Discordance between immunofluorescence and immunohistochemistry C4d staining and outcomes following heart transplantation. Issue 4 (16th February 2021) - Fujino, Takeo; Kumai, Yuto; Yang, Benjamin; Kalantari, Sara; Rodgers, Daniel; Henriksen, Kammi; Chang, Anthony; Husain, Aliya; Kim, Gene; Sayer, Gabriel; Uriel, Nir
Abstract: Background: Capillary deposition of C4d is an important marker of antibody‐mediated rejection (AMR) following heart transplantation (HT). There are two immunopathologic assay methods for detecting C4d: frozen‐tissue immunofluorescence (IF) and paraffin immunohistochemistry (IHC). The clinical significance of discrepancy between the results of IF and IHC has not been understood. Methods and results: We reviewed 2187 biopsies from 142 HT recipients who had biopsies with assessment of both IF and IHC staining. Among them, 103 (73%) patients had negative IF and IHC C4d staining (Negative Group) and 32 (23%) patients had positive IF but negative IHC staining (Discordant Group). At the time of positive biopsy, 6 (19%) Discordant patients had graft dysfunction, compared to 5 (5%) Negative patients ( p  = .022). Cumulative incidence of cellular rejection at 1 year was comparable (31% vs. 29%, p  = .46); however, cumulative incidence of AMR was significantly higher in the Discordant group (21% vs. 4%, p  = .004). Overall 1‐year survival was comparable (90% vs. 96%, p  = .24); however, freedom from heart failure (HF) was significantly lower in the Discordant group (70% vs. 96%, p  < .001). Conclusion: The Discordant group showed higher rates of graft dysfunction, AMR and HF admission than the Negative group.